2012
DOI: 10.1371/journal.pgen.1003043
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Physiological, and Motor Performance Defects in DMSXL Mice Carrying >1,000 CTG Repeats from the Human DM1 Locus

Abstract: Myotonic dystrophy type 1 (DM1) is caused by an unstable CTG repeat expansion in the 3′UTR of the DM protein kinase (DMPK) gene. DMPK transcripts carrying CUG expansions form nuclear foci and affect splicing regulation of various RNA transcripts. Furthermore, bidirectional transcription over the DMPK gene and non-conventional RNA translation of repeated transcripts have been described in DM1. It is clear now that this disease may involve multiple pathogenic pathways including changes in gene expression, RNA st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(173 citation statements)
references
References 56 publications
3
168
2
Order By: Relevance
“…In the present study, we have used DMSXL transgenic mice. These mice express the DMPK gene in a variety of tissues with a pattern similar to the patterns of the murine Dmpk gene in mice and the DMPK gene in human tissues (Huguet et al, 2012). To address whether the DMSXL transgenic mice animal model, which carry a long CTG repeat and display DM1 features (Gomes-Pereira et al, 2011), have respiratory problems, we tested and compared the breathing function in DMSXL and control mice.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the present study, we have used DMSXL transgenic mice. These mice express the DMPK gene in a variety of tissues with a pattern similar to the patterns of the murine Dmpk gene in mice and the DMPK gene in human tissues (Huguet et al, 2012). To address whether the DMSXL transgenic mice animal model, which carry a long CTG repeat and display DM1 features (Gomes-Pereira et al, 2011), have respiratory problems, we tested and compared the breathing function in DMSXL and control mice.…”
Section: Introductionmentioning
confidence: 82%
“…Mild missplicing of target RNA is observed in muscles and heart tissues. These molecular features of DM1-associated RNA toxicity were associated with high mortality, growth retardation and muscle defects (abnormal histopathology, reduced muscle strength and lower motor performances) (Huguet et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Thus, this is a precious model to study the time course of the disease with aging. It has been previously shown that DMSXL mice have reduced muscle strength, lower motor performances, peripheral neuropathy and respiratory impairments [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The originality of this model lies in the pattern of expression of the DMPK gene in DMSXL which is similar to DM1 patients including a high level of expression in the heart [13]. This model reproduces the main clinical characteristics observed in the human disease including reduced muscle strength, lower motor performances, peripheral neuropathy and respiratory impairments [13][14][15]. However, nothing is known about the cardiac phenotype of the DMSXL mouse.…”
Section: Introductionmentioning
confidence: 99%
“…DMSXL, derived from the DM300 line, is another transgenic model with >1000 CTG repeats due to intergenerational instability that led to ‘big jumps’ in CTG repeat number (Gomes-Pereira et al, 2007). These models exhibit different aspects of DM disease, such as muscle pathology, cardiac conduction problems, behavioral abnormalities accompanied by intranuclear RNA foci pathology and some tissue-specific splicing deficits (Gomes-Pereira et al, 2011; Hernandez-Hernandez et al, 2013; Huguet et al, 2012). Taken together, these mouse models serve as valuable tools to gain insight into DM disease mechanisms and for preclinical assessment of therapeutics targeting repeat expansion RNAs.…”
Section: Myotonic Dystrophymentioning
confidence: 99%